Slc7a14 Is Indispensable in Zebrafish Retinas - Zhuang, You-Yuan; Xiang, Lue; Wen, Xin-Ran; Shen, Ren-Juan; Zhao, Ning; Zheng, Si-Si; Han, Ru-Yi; Qu, Jia; Lu, Fan; Jin, Zi-Bing (Frontiers in Cell and Developmental Biology, 2019)
Previous study has identified SLC7A14 as a new causative gene of retinitis pigmentosa (RP). However, the role of SLC7A14 has not been fully characterized. The goal of this study was to investigate the biological features of slc7a14 in zebrafish. To determine the expression of slc7a14 in developing zebrafish, we performed in situ hybridization (ISH) and quantitative real-time PCR. Morpholino knockdown and overexpression experiments were performed to study the role of slc7a14 in zebrafish retinas. Immunostaining was carried out to observe structural changes. Visual motor responses (VMR) and optokinetic responses (OKR) were analyzed to assess visual behaviors. Terminal deoxynucleotidyl transferase (dUTP) nick-end labeling (TUNEL) staining was performed to survey apoptotic retinal cells. We found that slc7a14 was highly expressed in neuronal tissues, including the brain, spinal cord and retina, and that the expression levels increased during early embryogenesis. Consistently, ISH showed a similar expression pattern. Knockdown of slc7a14 led to dose-dependent microphthalmia that was reversed by overexpression. The immunostaining results revealed that the rod-specific protein zpr-3 and the retinal pigment epithelium-specific protein zpr-2 (decreased to 44.48%) were significantly suppressed in the slc7a14-silenced morphant. Notably, visual behaviors (the VMR and the OKR) were severely impaired in the slc7a14-deficient morphant, especially the VMR OFF response. In addition, apoptotic cells were observed in the retina at 3 days post fertilization (dpf) and 5 dfpf by TUNEL assay. Our results demonstrated that slc7a14 is essential for retinal function in zebrafish. Temporary silencing of slc7a14 in larvae led to severe visual impairments, consistent with the manifestations observed in RP patients. Our findings provide further insights into the genetic mechanisms of retinitis pigmentosa predisposition caused by SLC7A14 mutations.